Perancangan dan Uji Kinerja Mesin Peniris Keripik Kentang Kapasitas 20 kg Berbasis Sentrifugal untuk Industri Makanan Skala Kecil - Prasetyo, Dimas; Hermanto, Tino; Rokhim, Mochamad Iqbal (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
The small-scale food industry faces challenges at the drying stage of potato chips that affect product quality, texture, and shelf life. This research designed and tested a centrifugal force-based slicing machine with a capacity of 20 kg per cycle. The design method is carried out through an engineering approach that includes literature studies, AutoCAD design, prototype fabrication, and performance testing. The engine uses a 1 HP electric motor, a V-belt transmission system, and perforated stainless steel tubes. The test results showed that the engine was able to significantly lower the oil content in just ±30 seconds per cycle. This design is considered appropriate to increase production efficiency and competitiveness of MSME products.